Efektivitas Konseling REBT Pendekatan Teknik Self-Talk Untuk Menurunkan Tingkat Kecemasan Akademik Siswa Kelas X SMAN “A” Denpasar - Ni Kadek Rista Ary Putri; Ni Ketut Suarni; I Ketut Dharsana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to (1) find out the relationship between the use of the REBT counseling approach to self-talk techniques to reduce students' academic anxiety levels, (2) to know the benefits of the importance of self-talk techniques for students, (3) to find out the obstacles faced by students in the teaching and learning process in schools. The method used in this study was Pretest-Posttest Control Group Design. The subjects of this study were class X students of SMAN